“Il massimo di diversità nel minimo spazio”. Per una "Weltliteratur" dei romanzieri nell’età contemporanea (Comparatismi, 2025)
This article examines the contribution made by several contemporary novelists to the debate on World Literature. In their critical essays, authors such as Milan Kundera, Carlos Fuentes, Alejo Carpentier and Adam Thirlwell have reaffirmed the transnational vocation of the novel under the guiding influence of Cervantes. By interpreting their hypotheses within the framework of a precise theoretical model and reconstructing the critical debate they have generated, the aim of the article is to demonstrate the strong relevance of the comparative approach to the study of a genre such as the novel. It will also show how novelists respond to the risk of a renewed nationalization of literary studies, identifying in their engagement with other media an opportunity to rethink the tools and aims that define the novel as a genre.
Keywords: Novel; Genre; World Literature; Comparative Literature; Essay